An ultra-high alloyed austenitic stainless steel bloom and a method for producing the same

CN122979757APending Publication Date: 2026-10-27CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611408490.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

调研表明,高锰钢生产过程中使用普碳钢保护渣进行浇铸时,渣金反应性问题严重,影响保护渣的成分和性能,甚至无法完成单炉浇铸,铸坯表面质量不佳

Benefits of technology

[0039]1、基于本发明的方案得到的超高合金化奥氏体不锈钢大方坯具有良好的表面质量,无裂纹、折叠、结疤等缺陷产生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979757A_ABST
    Figure CN122979757A_ABST
Patent Text Reader

Abstract

The application provides a kind of super-high alloying austenitic stainless steel and its production method, the stainless steel includes the following components: 0.45~0.55% of C, 0.05~0.2% of Si, 29~30% of Mn, 6~8% of Cr, 5~6% of Ni, 3~4% of Mo, the balance of Fe and inevitable impurities.The production method includes:1) the qualified molten steel is poured, wherein the superheat of the first pouring molten steel is controlled to be 10~15℃, and the superheat of the continuously cast molten steel is 15~35℃;the water flow of crystallizer is 2800~3400 L / min, and the temperature difference of cooling water is 3.5~5℃;the composition of crystallizer protecting slag is: SiO2 24~35%, CaO 20~30%, Al2O3 3.0~7.0%, Na2O 7.5~12%, F 3.0~9.0%, MnO 10~14%, Li2O 6~8%, MgO≤2.5%, Fe2O3≤1.5%, C 3~17%;2) the specific water quantity of secondary cooling stage is controlled to be 0.3~0.55 L / Kg;3) the reduction of each stage of light pressing is 1.5~3 mm.The stainless steel big billet of the application has good surface quality, and no cracks, folds, scarring and other defects are generated.The protecting slag has the characteristics of good spreading, uniform and stable slag melting, no agglomeration, etc., and no cracking and other defects are generated during rolling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of stainless steel production technology, specifically relating to a large square billet of ultra-high alloyed austenitic stainless steel and its production method. Background Technology

[0002] Since its invention in 1882 by British metallurgist Robert Abbott Hadfield, high-manganese steel has been widely used in mining machinery, railway frogs, and crushing equipment due to its excellent work hardening ability, good low-temperature toughness, and wear resistance. Traditional high-manganese steel (represented by Mn13) typically has a manganese content of 11% to 14% and a carbon content of 1.0% to 1.4%. Its work hardening mechanism mainly relies on the synergistic effect of deformation-induced twinning and dislocation slip.

[0003] In recent years, with the rapid development of the global clean energy industry, applications such as cryogenic liquid hydrogen storage and liquefied natural gas storage and transportation have placed higher demands on cryogenic steel. Studies have shown that when the manganese content is increased to 25%–30%, high-manganese steel can still maintain good impact toughness and tensile strength at low temperatures (-196℃), with performance comparable to 9Ni steel, but with significantly reduced alloy costs. To further optimize overall performance, researchers have attempted to add alloying elements such as chromium, nickel, and molybdenum to high-manganese steel. When the manganese content reaches 29%–30%, and Cr 6%–8%, Ni 5%–6%, and Mo 3%–4% are added simultaneously, the total alloying element content exceeds 44%, and its low-temperature toughness and strength are expected to be significantly improved. However, this also presents unprecedented challenges to the material preparation technology.

[0004] Continuous casting of high-manganese steel has long been a recognized technical challenge in the industry. Research indicates that when using plain carbon steel protective slag for casting during high-manganese steel production, the slag-metal reactivity problem is severe, affecting the composition and performance of the protective slag, and even making single-furnace casting impossible, resulting in poor billet surface quality. The main reasons for the difficulties in continuous casting of high-manganese steel are as follows: 1) The physical properties of high-manganese steel lead to extremely high crack sensitivity; 2) The intense slag-metal reaction damages the performance of the protective slag; 3) The extremely wide solidification range dramatically increases the risk of segregation and cracking.

[0005] In summary, there is an urgent need to find a production method that can improve the quality of large billets of ultra-high alloyed austenitic stainless steel. Summary of the Invention

[0006] To address the problems existing in the prior art, this invention provides a large billet of ultra-high alloyed austenitic stainless steel and its production method, aiming to improve the quality of the large billet by optimizing the protective slag, continuous casting process, heating regime, etc.

[0007] According to one aspect of the present invention, an ultra-high alloyed austenitic stainless steel is provided, comprising, by weight: 0.45-0.55% C, 0.05-0.2% Si, 29-30% Mn, 6-8% Cr, 5-6% Ni, 3-4% Mo, with the balance being Fe and unavoidable impurities.

[0008] As a preferred embodiment of the ultra-high alloyed austenitic stainless steel of the present invention, the composition further includes ≤0.005% P and ≤0.015% S.

[0009] According to another aspect of the present invention, a method for producing ultra-high alloyed austenitic stainless steel is provided, comprising:

[0010] 1) Pouring molten steel with qualified composition, wherein,

[0011] The superheat of the molten steel in the first furnace is controlled at 10~15℃, and the superheat of the molten steel in the continuous casting furnace is controlled at 15~35℃, with a casting speed of 0.39~0.42 m / min;

[0012] The flow rate of the crystallizer water is controlled at 2800~3400 L / min, and the temperature difference between the inlet and outlet of the cooling water is 3.5~5℃;

[0013] The insertion depth of the submersible nozzle is controlled to be 160~230mm, and the liquid level fluctuation in the crystallizer is controlled to be -10~+10mm;

[0014] The protective slag used in the crystallizer comprises the following components and contents: SiO2 24~35%, CaO 20~30%, Al2O3 3.0~7.0%, Na2O 7.5~12%, F - 3.0~9.0%, MnO 10~14%, Li2O 6~8%, MgO≤2.5%, Fe2O3≤1.5%, C3~17%;

[0015] 2) In the secondary cooling stage, a weak secondary cooling water distribution mode is adopted, and the specific water volume is controlled at 0.3~0.55L / Kg;

[0016] 3) In the light pressing stage, a 4-stage pressing mode is adopted, with each stage having a pressing amount of 1.5~3mm.

[0017] As a preferred embodiment of the production method of ultra-high alloyed austenitic stainless steel of the present invention, the stainless steel is cast to obtain a large square billet of (300~340) mm × (400~500) mm.

[0018] As a preferred embodiment of the production method of ultra-high alloyed austenitic stainless steel of the present invention, the production method further includes a step of heat treatment of the cooled billet, specifically including: heating the billet in three sections, wherein the preheating section temperature is ≤850℃ and the heating rate is ≤70℃ / h, the 850~950℃ range and the heating rate is 40~70℃ / h, the 950~1150℃ range and the heating rate is 70~100℃ / h, the soaking section temperature is 1120~1250℃ and the heating rate is ≤60℃ / h, after reaching the target temperature, the holding time is 2~4h, and the total heating time of the three sections is ≥8h.

[0019] As a preferred embodiment of the production method of ultra-high alloyed austenitic stainless steel of the present invention, the production method further includes a step of rolling the heat-treated billet, specifically including: heating the heat-treated and cooled billet, wherein heating stage I is 930~1050℃ and heating time is 1~1.5h, heating stage II is 1000~1220℃ and heating time is 1.5~2h, soaking stage is 1120~1250℃ and heating time is 1.5~2h, and the total heating time is 3.5~5.5h, controlling the initial rolling temperature to be 980~1100℃ and the wire drawing temperature to be 900~950℃.

[0020] As a preferred embodiment of the production method of ultra-high alloyed austenitic stainless steel of the present invention, the billet size for rolling is (140~160) mm × (140~160) mm.

[0021] Based on the proposed solution of this invention, since the total alloy content exceeds 44%, especially the Mn content of 29-30%, which is significantly higher than that of traditional high-manganese steel, traditional protective slag cannot meet the casting requirements of the ultra-high alloyed austenitic stainless steel of this invention. This invention determines the upper limit of MnO content in the protective slag based on solidification behavior characteristics, specifically as follows: The solidification mode of the steel grade of this invention is "liquid state → liquid state + austenite → single austenite", with both the primary and final phases being austenite (FCC_A1), and no δ-ferrite precipitation throughout the process. Because the linear shrinkage coefficient of austenite (approximately 2.4-3.5%) is significantly greater than that of δ-ferrite, the solidification shrinkage stress generated during solidification shrinkage is greater. Simultaneously, due to the single solidification path (no peritectic reaction), solidification shrinkage is concentrated in the mushy region, requiring extremely high uniformity of heat flow within the crystallizer. If the heat transfer of the protective slag is uneven, and the local heat flux density difference is too large, non-uniform shrinkage will occur on the surface of the billet shell, leading to thermal stress concentration. The high-temperature tensile strength of this steel grade at 1200℃ is only 20~30MPa, far lower than that of ordinary carbon steel, making it extremely prone to longitudinal and corner cracks at points of thermal stress concentration. When the MnO content in the protective slag is too high (>14%), the crystallization temperature of the protective slag increases significantly, the proportion of crystals in the slag film increases, and the heat flux density becomes uneven. Under the high shrinkage stress conditions of solidification of single austenite, the temperature gradient on the surface of the billet will be further amplified, leading to thermal stress concentration and inducing longitudinal cracks.

[0022] It is particularly important to note that the MnO content in this invention is limited to 14%, lower than the MnO content (15-20%) in conventional high-manganese steel protective slag in the prior art. This is not a conservative or regressive approach, but rather determined by the fundamental difference in solidification mode between the steel grade of this invention and conventional high-manganese steel. Conventional high-manganese steel (Mn≤25%) typically exhibits δ-ferrite precipitation during solidification, and the linear shrinkage coefficient of δ-Fe is relatively small (approximately 1.0-1.5%), which can buffer solidification shrinkage stress to a certain extent. However, the steel grade of this invention, as confirmed by Factsage thermodynamic calculations, follows a single austenite solidification path of L→L+γ→γ, with no δ-ferrite precipitation throughout the entire process. The linear shrinkage coefficient of austenite (2.4-3.5%) is more than twice that of δ-Fe, resulting in concentrated solidification shrinkage stress without any phase transformation buffering. Under these conditions, any slight deterioration in the heat transfer uniformity of the protective slag will be drastically amplified. When MnO > 14%, the crystallization temperature of the protective slag increases significantly, the proportion of crystals in the slag film increases, and the heat flux density becomes uneven. This, combined with the large shrinkage stress from the solidification of a single austenite, directly leads to severe non-uniform shrinkage and thermal stress concentration on the surface of the billet shell. The high-temperature tensile strength of this steel grade at 1200℃ is only 20-30 MPa, far lower than that of ordinary carbon steel, making it completely unable to resist this stress. Ultimately, this manifests as a concentrated outbreak of longitudinal and corner cracks. Therefore, this invention sets the upper boundary of the MnO content at 14%, a rigid constraint imposed on the heat transfer uniformity of the protective slag by the unique solidification characteristics of a single austenite in this steel grade. This is fundamentally different from conventional high-manganese steel protective slag solutions in existing technologies.

[0023] However, when the MnO content decreases, the viscosity-reducing effect of the protective slag decreases, the fluidity decreases, which is not conducive to the uniform distribution of the slag film and the lubrication time is prolonged due to the solidification "tailing" effect caused by dendrite segregation. Therefore, if the content is too low, it will affect the performance of the protective slag.

[0024] To address the aforementioned drawbacks, this invention proposes to compensate by increasing the Li₂O content in the protective slag. Experimental results show that when the Li₂O content is increased to 6% or higher, the protective slag can maintain an ultra-low viscosity (0.10~0.50 Pa·s at 1300℃) throughout the crystallization process, effectively compensating for the prolonged lubrication time caused by the solidification "tailing" effect due to dendrite segregation. However, based on this invention, it was also found that a higher Li₂O content is not always better. When it is too high (>8%), the melting point and viscosity of the protective slag become too low, leading to problems such as an excessively thick liquid slag layer, increased risk of slag entrapment, and excessively rapid heat transfer.

[0025] Considering the extent of the compensation effect of Li2O and to avoid new problems with the protective slag, the lower limit of MnO content was finally determined to be 10%.

[0026] In the solution of this invention, the water flow rate of the crystallizer is controlled at 2800~3400L / min, and the specific basis is as follows:

[0027] First, for high-manganese steel, the thermal conductivity is about 1 / 6 that of 20 steel, and the linear shrinkage is 2.4%~3.5%, which is more than twice that of carbon steel. When the water flow rate in the crystallizer is less than 2800L / min, the cooling intensity is insufficient, the initial billet shell grows too slowly, and the billet shell thickness is too thin. Under the static pressure of molten steel, bulging deformation or even steel leakage accidents are likely to occur.

[0028] Secondly, when the water flow rate in the crystallizer exceeds 3400 L / min, the cooling intensity is too high, and the temperature gradient between the surface and interior of the billet increases sharply (reaching 200~300℃ / mm). The resulting thermal stress can easily exceed the material's strength limit at high temperatures (the tensile strength of high-manganese steel at 1200℃ is only 20~30 MPa), leading to the formation of longitudinal cracks. Weak cooling promotes uniform cooling and avoids the formation of gaps due to shrinkage during the solidification of molten steel, which generates significant thermal resistance and causes longitudinal cracks on the billet surface.

[0029] In this invention, the temperature difference between the inlet and outlet water of the crystallizer is controlled at 3.5~5.0℃. This parameter reflects the overall effect of the crystallizer's cooling intensity: a temperature difference below 3.5℃ indicates insufficient cooling intensity; a temperature difference above 5.0℃ indicates excessive cooling intensity. By controlling the temperature difference between the inlet and outlet water, the heat transfer rate of the crystallizer can be indirectly controlled, thereby achieving precise regulation of the billet growth rate.

[0030] In the present invention, to avoid cracking of ultra-high alloyed austenitic stainless steel, it is necessary to control the secondary cooling water ratio. This is because when the secondary cooling water ratio is too low (below 0.30 L / kg), the cooling intensity is too low, and the temperature of the billet in the secondary cooling zone is too high (the surface temperature may exceed 1100°C), resulting in coarsening of columnar grains, increased central segregation, and the billet is prone to straightening cracks due to insufficient high-temperature strength during straightening. When the secondary cooling water ratio is too high (above 0.55 L / kg), the cooling intensity is too high, and the surface temperature of the billet drops sharply (the cooling rate may exceed 50°C / s), the temperature gradient between the surface and the core increases sharply, and the resulting thermal stress exceeds the high-temperature strength of the material, leading to the generation of surface cracks. At the same time, excessive secondary cooling will cause martensitic phase transformation on the surface of the billet, further deteriorating the surface quality. In view of this, the secondary cooling water ratio in the present invention should be controlled at 0.3~0.55 L / kg for ultra-high alloy steel with a solidification range of 102℃, so as to avoid crack propagation caused by uneven shrinkage in a wide solidification range.

[0031] The light reduction technique compensates for solidification shrinkage and reduces central shrinkage cavities and segregation by applying mechanical reduction at the end of solidification. Its core lies in determining the optimal reduction amount. Because the steel grade of this invention has a wide solidification range of up to 102°C, and the length of the mushy zone (mushy zone length = solidification range / temperature gradient; the mushy zone length of this invention is approximately 34~51 mm) is significantly greater than that of conventional high-manganese steel (solidification range approximately 50°C, mushy zone length approximately 17~25 mm), a specific light reduction method needs to be specified for adaptation. Experiments show that the critical strain value of the steel grade of this invention is approximately 0.5%~0.8%, far lower than that of traditional steel grades. When the single-stage reduction exceeds 3 mm, for ultra-high alloy steel grades with a mushy zone length of 34~51 mm, the strain borne by the billet shell exceeds its critical strain value, easily leading to internal cracks in the vulnerable area at the solidification front, resulting in an extremely high risk of cracking. However, the reduction amount should not be too low (<1.5 mm), otherwise it cannot effectively compensate for solidification shrinkage, and the effect of reducing central segregation and shrinkage cavities is not significant. This invention adopts a strategy of "small reduction (2~3mm per segment) and multiple segments (four segments)". The reduction of 2~3mm per segment can control the strain within the range of 0.2%~0.4%, which is lower than the critical strain value. At the same time, the cumulative reduction of the four continuous segments (8~12mm) is sufficient to effectively compensate for solidification shrinkage and reduce central segregation.

[0032] Appropriately reducing superheat can improve macroscopic segregation in continuously cast billets, reduce the spacing of secondary dendrite arms in the solidified structure of the billets, and reduce the width of ferrite bands in the banded structure after rolling. Under low superheat conditions, molten steel enters the solidification state rapidly after entering the crystallizer, the temperature gradient decreases, the driving force for columnar crystal growth decreases, and it is conducive to promoting the formation of equiaxed crystals. For the steel grade of this invention, a superheat of more than 15°C in the first heat will not only aggravate central segregation, but also lead to a further increase in the length of the mushy zone, which will multiply the risk of cracking. However, a superheat of less than 10°C will also result in poor molten steel fluidity, a significant increase in the risk of nozzle blockage, and is not conducive to temperature homogenization in the tundish, and is prone to freezing accidents in the early stage of casting. For continuous casting heats, since the tundish is already in a thermally stable state, the superheat control range is 15~35°C. It should be noted that relaxing the upper limit of superheat for consecutive casting cycles to 35°C does not mean that the physical mechanism of increased segregation has been eliminated, but rather it is based on a trade-off made in engineering practice: consecutive casting cycles need to ensure stable casting speed and uniform consumption of protective slag. When the superheat is below 15°C, the molten steel has insufficient fluidity and the casting speed fluctuates more, which in turn affects the stability of the surface quality of the billet. Experiments show that within the range of 15~35°C, the increase in the degree of segregation and the length of the mushy zone is gradual and controllable, and the billet quality still meets the requirements. However, when the superheat exceeds 35°C, columnar crystal coarsening, central segregation deteriorates sharply, the mushy zone is significantly prolonged, and the risk of cracking increases sharply. Therefore, 15~35°C is the optimal balance window for consecutive casting cycles, optimized through extensive experiments, between "ensuring the stability of continuous casting" and "controlling the risk of segregation and cracking."

[0033] After cutting, the billets obtained from continuous casting undergo pit cooling treatment for at least 48 hours. Hot billets are preheated in the pit, and the temperature upon exiting the pit is ≤50℃. Because the coefficient of thermal expansion of high-manganese steel is approximately 50% higher than that of ordinary steel, the cooling process must be slow and uniform to prevent cracking. Pit cooling effectively controls the cooling rate of the billet, avoiding thermal stress cracks caused by excessively rapid cooling.

[0034] The steel grade of this invention has poor thermal conductivity, which leads to a greater temperature difference between the surface and the core, thus increasing thermal stress. When the preheating temperature exceeds 850°C, the surface of the billet experiences a high heat flux density in the initial stage of furnace entry, causing a rapid rise in surface temperature, while the core temperature remains relatively low. The temperature difference between the surface and the core can reach 500-800°C. The resulting thermal stress can easily exceed the elastic limit of the steel, causing torsional deformation, or even exceeding the tensile strength, resulting in cracks. This invention controls the preheating temperature to ≤850°C and the heating rate to ≤70°C / h, ensuring that the temperature difference between the surface and the core of the billet is controlled within a reasonable range (≤300°C) in the initial stage of furnace entry, thus avoiding thermal stress cracking. During the initial heating phase, as the temperature rises, the plasticity of the steel gradually improves, allowing for a gradual increase in the allowable heating rate. The 850–950℃ range remains within the low-temperature brittleness zone of high-manganese steel, requiring the heating rate to be controlled at a relatively low level of 40–70℃ / h. In the 950–1150℃ range, the plasticity of high-manganese steel improves significantly, allowing for a moderate increase in the heating rate to 70–100℃ / h. This segmented control improves heating efficiency while ensuring safety. The purpose of the holding stage is to fully homogenize the temperature of the billet core. When the homogenization temperature is below 1120℃, the billet core temperature is difficult to reach the initial rolling temperature (approximately 980–1100℃), and austenitization is insufficient. When the homogenization temperature is above 1250℃, excessive grain growth occurs (austenite grains may exceed 200μm), affecting the subsequent rolling microstructure and the final product performance. The present invention controls the temperature of the soaking zone at 1120~1250℃, which can ensure sufficient austenitization and temperature uniformity, while avoiding excessive grain growth.

[0035] For high-alloy steel parts with large cross-sections, if the heating rate is too high, the thermal stress is prone to exceed the elastic limit of the steel, resulting in torsional deformation, or even exceeding the tensile strength of the steel, leading to cracks. For the large square billet of this invention with a cross-sectional size of (300~340) mm × (400~500) mm, sufficient time is required for the core temperature to reach the homogenization temperature. Based on this, the total heating time should be ≥8h.

[0036] In the present invention, when the initial rolling temperature is below 980℃, high-manganese steel is in the low-temperature brittle zone, and the deformation resistance increases sharply (the deformation resistance can reach 250~350MPa), the mill load exceeds the limit, and surface cracks are easily generated. When the initial rolling temperature is above 1100℃, although the deformation resistance decreases, the grains grow excessively, and the surface oxidation is severe. The present invention controls the initial rolling temperature at 980~1100℃, which not only ensures the smooth progress of the rolling process, but also avoids the triple risks in subsequent rolling and final service processes caused by excessive grain growth—increased tendency of grain boundary cracking during rolling (surface cracks, edge cracks), severe deterioration of ultra-low temperature impact toughness (increased risk of brittle fracture), and mixed grain structure (non-uniform mechanical properties) in the product.

[0037] It should be noted that the operation methods and parameter controls not mentioned in each process segment of this invention are all based on relevant means known in the art.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The ultra-high alloyed austenitic stainless steel billet obtained based on the solution of the present invention has good surface quality and is free from defects such as cracks, folds, and scabs.

[0040] 2. The protective slag used in this invention has the characteristics of good spreadability, uniform and stable slag formation, and no clumping by optimizing the product composition and content.

[0041] 3. The ultra-high alloyed austenitic stainless steel obtained based on the heat treatment and rolling process of this invention is free from defects such as cracking. Attached Figure Description

[0042] Figure 1 This is the protective slag surface of the crystallizer in Embodiment 1 of the present invention;

[0043] Figure 2 The low-magnification microstructure of the cast billet in Embodiment 1 of the present invention;

[0044] Figure 3 This is the protective slag surface of the crystallizer in Comparative Example 1 of the present invention;

[0045] Figure 4 This is the low-magnification microstructure of the billet in Comparative Example 2 of the present invention. Detailed Implementation

[0046] The technical solutions described below in conjunction with the embodiments will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0047] Example 1

[0048] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.47%, Si 0.12%, Mn 29.6%, Cr 7.1%, Ni 5.4%, Mo 3.5%, P 0.004%, S 0.008%, with the balance being Fe and unavoidable impurities.

[0049] The production method includes:

[0050] 1) Continuous casting process

[0051] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 420mm.

[0052] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 12°C, and the casting speed was 0.4 m / min;

[0053] The crystallizer water flow rate is controlled at 3100 L / min, and the inlet and outlet temperature difference of the cooling water is 4.2℃;

[0054] The insertion depth of the submersible nozzle is controlled to be 190 mm, and the liquid level fluctuation in the crystallizer is controlled to be -5 to +5 mm.

[0055] The protective slag used in the crystallizer comprises the following components and contents: SiO2 28.5%, CaO 24.0%, Al2O3 5.0%, Na2O 9.5%, F - The composition is 6.0%, MnO 12.0%, Li₂O 7.0%, MgO 1.8%, Fe₂O₃ 0.8%, C 5.0%, with the balance being unavoidable impurities. The basicity (CaO / SiO₂) of the protective slag is 0.84, and the viscosity at 1300℃ is 0.25 Pa·s.

[0056] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.42L / Kg;

[0057] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.2mm, 2.8mm, 2.2mm, and 2.8mm for each stage, and a cumulative pressing amount of 10.0mm.

[0058] 2) Heat treatment process

[0059] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 820℃ at a rate of 65℃ / h; the first heating section was heated to 895℃ at a rate of 55℃ / h; the second heating section was heated to 1055℃ at a rate of 85℃ / h; and the third heating section was heated to 1180℃ at a rate of 55℃ / h. After reaching the heating temperature, the billet was held at that temperature for 3 hours. The total heating time for the three sections was 8.5 hours.

[0060] 3) Rolling process

[0061] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 150mm×150mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0062] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1000℃, heating time 1.2h; Heating section II temperature 1120℃, heating time 1.3h; Soaking section temperature 1180℃, holding time 1.5h; total heating time 4.0 hours. The initial rolling temperature is 1040℃, and the wire drawing temperature is 925℃.

[0063] The slag surface is well protected, spreads well, and the slag is uniformly and stably formed without clumping or obvious sintering. Figure 1 The surface quality of the cast billets is good. Except for a slight depression in the first billet, the surface of the remaining cast billets is normal, with no longitudinal cracks or corner cracks. The surface quality after rolling is good, with no defects such as cracks, folds, or scabs.

[0064] Example 2

[0065] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.49%, Si 0.10%, Mn 29.8%, Cr 7.2%, Ni 5.5%, Mo 3.6%, P 0.003%, S 0.006%, with the balance being Fe and unavoidable impurities.

[0066] The production method includes:

[0067] 1) Continuous casting process

[0068] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 420mm.

[0069] As for the molten steel in the continuous casting furnace, the superheat of the molten steel is controlled at 18℃ and the casting speed is 0.39 m / min;

[0070] The crystallizer water flow rate is controlled at 3200 L / min, and the inlet and outlet temperature difference of the cooling water is 4.5℃;

[0071] The insertion depth of the submersible nozzle is controlled to be 180 mm, and the liquid level fluctuation in the crystallizer is controlled to be -4 to +4 mm.

[0072] The protective slag used in the crystallizer comprises the following components and contents: SiO2 30.0%, CaO 22.0%, Al2O3 4.5%, Na2O 10.0%, F - The composition is 5.5%, MnO 12.5%, Li2O 6.8%, MgO 2.0%, Fe2O3 0.7%, C 4.8%, with the balance being unavoidable impurities. The basicity (CaO / SiO2) of the protective slag is 0.73, and the viscosity at 1300℃ is 0.28 Pa·s.

[0073] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.38L / kg;

[0074] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.5mm, 2.5mm, 2.0mm, and 3.0mm for each stage, and a cumulative pressing amount of 10.0mm.

[0075] 2) Heat treatment process

[0076] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 830℃ at a rate of 60℃ / h; the first heating section was heated to 900℃ at a rate of 50℃ / h; the second heating section was heated to 1060℃ at a rate of 80℃ / h; and the third heating section was heated to 1160℃ at a rate of 50℃ / h. After reaching the heating temperature, the billet was held at that temperature for 3.5 hours. The total heating time for the three sections was 9.0 hours.

[0077] 3) Rolling process

[0078] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 145mm×145mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0079] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1020℃, heating time 1.1h; Heating section II temperature 1150℃, heating time 1.2h; Soaking section temperature 1160℃, holding time 1.8h; total heating time 4.1 hours. The initial rolling temperature is 1050℃, and the wire drawing temperature is 915℃.

[0080] The slag surface was well protected, with good spreadability, uniform and stable slag formation, no clumping, and no obvious sintering. The surface quality of the cast billet was good, with no longitudinal cracks or corner cracks. The surface quality after rolling was also good, with no defects such as cracks, folds, or scale. This embodiment demonstrates that the technical solution of the present invention still has good feasibility under continuous casting conditions.

[0081] Example 3

[0082] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.45%, Si 0.18%, Mn 29.2%, Cr 6.5%, Ni 5.1%, Mo 3.2%, P 0.005%, S 0.010%, with the balance being Fe and unavoidable impurities.

[0083] The production method includes:

[0084] 1) Continuous casting process

[0085] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 340mm × 480mm.

[0086] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 10°C, and the casting speed was 0.39 m / min;

[0087] The crystallizer water flow rate is controlled at 2800 L / min, and the inlet and outlet temperature difference of the cooling water is 3.5℃;

[0088] The insertion depth of the submersible nozzle is controlled to be 160 mm, and the liquid level fluctuation in the crystallizer is controlled to be -8 to +8 mm.

[0089] The protective slag used in the crystallizer comprises the following components and contents: SiO2 24.0%, CaO 29.0%, Al2O3 6.5%, Na2O 8.0%, F - The composition is as follows: 8.5% MnO, 10.5% Li2O, 6.2% MgO, 2.4% Fe2O3, 1.2% C, 15.0%, with the balance being unavoidable impurities. The basicity (CaO / SiO2) of the protective slag is 1.21, and the viscosity at 1300℃ is 0.45 Pa·s.

[0090] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.30L / kg;

[0091] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 1.5mm, 2.0mm, 1.5mm, and 2.5mm for each stage, and a cumulative pressing amount of 7.5mm.

[0092] 2) Heat treatment process

[0093] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 800℃ at a rate of 70℃ / h; the first heating section was heated to 880℃ at a rate of 60℃ / h; the second heating section was heated to 1040℃ at a rate of 90℃ / h; and the third heating section was heated to 1120℃ at a rate of 60℃ / h. After reaching the heating temperature, the billet was held at that temperature for 4 hours. The total heating time for the three sections was 8.0 hours.

[0094] 3) Rolling process

[0095] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a billet with a billet size of 160mm×160mm. After rolling, the billet is cooled by a windproof stacking method.

[0096] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 930℃, heating time 1.5h; Heating section II temperature 1000℃, heating time 1.5h; Soaking section temperature 1120℃, holding time 2.0h; total heating time 5.0h. The initial rolling temperature is 1080℃, and the wire drawing temperature is 900℃.

[0097] The slag surface is well protected, with good spreadability, uniform and stable slag formation, no clumping, and no obvious sintering. The surface quality of the cast billets is good; except for a slight depression in the first billet, the surfaces of the remaining billets are normal, without longitudinal cracks or corner cracks. The surface quality after rolling is good, without defects such as cracks, folds, or scabs.

[0098] Example 4

[0099] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.53%, Si 0.06%, Mn 29.9%, Cr 7.8%, Ni 5.8%, Mo 3.9%, P 0.003%, S 0.005%, with the balance being Fe and unavoidable impurities.

[0100] The production method includes:

[0101] 1) Continuous casting process

[0102] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is then cast to obtain a large square billet with dimensions of 300mm × 400mm.

[0103] As for the molten steel in the continuous casting furnace, the superheat of the molten steel is controlled at 32℃ and the casting speed is 0.42 m / min;

[0104] The crystallizer water flow rate is controlled at 3400 L / min, and the inlet and outlet temperature difference of the cooling water is 5.0℃;

[0105] The insertion depth of the submersible nozzle is controlled to be 220 mm, and the liquid level fluctuation in the crystallizer is controlled to be -6 to +6 mm.

[0106] The protective slag used in the crystallizer comprises the following components and contents: SiO2 34.0%, CaO 20.5%, Al2O3 3.5%, Na2O 11.5%, F - The composition is 3.5%, MnO 13.5%, Li2O 7.8%, MgO 1.5%, Fe2O3 0.6%, C 4.0%, with the balance being unavoidable impurities. The basicity (CaO / SiO2) of the protective slag is 0.60, and the viscosity at 1300℃ is 0.15 Pa·s.

[0107] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.52L / kg;

[0108] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 3.0mm, 2.5mm, 3.0mm, and 2.0mm for each stage, and a cumulative pressing amount of 10.5mm.

[0109] 2) Heat treatment process

[0110] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 845℃ at a rate of 50℃ / h; the first heating section was heated to 910℃ at a rate of 65℃ / h; the second heating section was heated to 1080℃ at a rate of 95℃ / h; and the soaking section was heated to 1240℃ at a rate of 45℃ / h. After reaching the soaking temperature, the billet was held at that temperature for 2 hours. The total heating time for the three sections was 9.0 hours.

[0111] 3) Rolling process

[0112] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 140mm×140mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0113] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1040℃, heating time 1.0h; Heating section II temperature 1210℃, heating time 1.0h; Soaking section temperature 1240℃, holding time 1.0h; total heating time 3.5 hours. The initial rolling temperature is 1090℃, and the wire drawing temperature is 945℃.

[0114] The slag surface was well protected, with good spreadability, uniform and stable slag formation, no clumping, and no obvious sintering. The surface quality of the cast billet was good, with no longitudinal cracks or corner cracks. The surface quality after rolling was also good, with no defects such as cracks, folds, or scabs. This embodiment demonstrates that the technical solution of the present invention can still operate stably under the condition of high superheat (32°C) in consecutive casting furnaces.

[0115] Example 5

[0116] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.51%, Si 0.14%, Mn 29.4%, Cr 6.8%, Ni 5.6%, Mo 3.3%, P 0.004%, S 0.007%, with the balance being Fe and unavoidable impurities.

[0117] The production method includes:

[0118] 1) Continuous casting process

[0119] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 460mm.

[0120] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 14°C, and the casting speed was 0.41 m / min.

[0121] The crystallizer water flow rate is controlled at 3000 L / min, and the inlet and outlet temperature difference of the cooling water is 3.8℃;

[0122] The insertion depth of the submersible nozzle is controlled to be 200 mm, and the liquid level fluctuation in the crystallizer is controlled to be -3 to +3 mm.

[0123] The protective slag used in the crystallizer comprises the following components and contents: SiO2 26.0%, CaO 26.0%, Al2O3 5.5%, Na2O 8.5%, F - The composition is 7.0%, MnO 11.0%, Li2O 7.5%, MgO 1.6%, Fe2O3 0.9%, C 12.0%, with the balance being unavoidable impurities. The basicity (CaO / SiO2) of the protective slag is 1.00, and the viscosity at 1300℃ is 0.32 Pa·s.

[0124] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.45L / kg;

[0125] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.0mm, 3.0mm, 2.0mm, and 2.5mm for each stage, and a cumulative pressing amount of 9.5mm.

[0126] 2) Heat treatment process

[0127] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 810℃ at a rate of 62℃ / h; the first heating section was heated to 885℃ at a rate of 52℃ / h; the second heating section was heated to 1045℃ at a rate of 82℃ / h; and the soaking section was heated to 1200℃ at a rate of 52℃ / h. After reaching the soaking temperature, the billet was held at that temperature for 3.2 hours. The total heating time for the three sections was 8.8 hours.

[0128] 3) Rolling process

[0129] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a billet with a size of 155mm×155mm. After rolling, the billet is cooled by a sheltered stacking method.

[0130] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 980℃, heating time 1.3h; Heating section II temperature 1080℃, heating time 1.4h; Soaking section temperature 1200℃, holding time 1.6h; total heating time 4.3 hours. The initial rolling temperature is 1030℃, and the wire drawing temperature is 930℃.

[0131] The slag surface is well protected, with good spreadability, uniform and stable slag formation, no clumping, and no obvious sintering. The surface quality of the cast billets is good; except for a slight depression in the first billet, the surfaces of the remaining billets are normal, without longitudinal cracks or corner cracks. The surface quality after rolling is good, without defects such as cracks, folds, or scabs.

[0132] Comparative Example 1

[0133] This comparative example uses conventional high-manganese steel continuous casting protective slag (the content of MnO and Li2O is lower than that of this invention) to verify the necessity of the protective slag of this invention.

[0134] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.48%, Si 0.11%, Mn 29.5%, Cr 7.0%, Ni 5.3%, Mo 3.4%, P 0.004%, S 0.007%, with the balance being Fe and unavoidable impurities.

[0135] The production method includes:

[0136] 1) Continuous casting process

[0137] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 420mm.

[0138] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 12°C, and the casting speed was 0.40 m / min;

[0139] The crystallizer water flow rate is controlled at 3100 L / min, and the inlet and outlet temperature difference of the cooling water is 4.2℃;

[0140] The insertion depth of the submersible nozzle is controlled to be 190 mm, and the liquid level fluctuation in the crystallizer is controlled to be -5 to +5 mm.

[0141] The molded crystallizer uses conventional high-manganese steel continuous casting protective slag, which, by mass percentage, is: SiO2 32.0%, CaO2 4.0%, Al2O3 8.0%, Na2O 5.0%, F⁻ 4.0%, MnO 1.5%, Li2O 0.5%, MgO 3.0%, Fe2O3 1.2%, C 8.0%, with the balance being unavoidable impurities. The basicity of the protective slag (CaO / SiO2) is 0.75.

[0142] The specific water volume during the secondary cooling stage is controlled at 0.42 L / kg;

[0143] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.2mm, 2.8mm, 2.2mm, and 2.8mm for each stage, and a cumulative pressing amount of 10.0mm.

[0144] 2) Heat treatment process

[0145] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 820℃ at a rate of 65℃ / h; the first heating section was heated to 895℃ at a rate of 55℃ / h; the second heating section was heated to 1055℃ at a rate of 85℃ / h; and the third heating section was heated to 1180℃ at a rate of 55℃ / h. After reaching the heating temperature, the billet was held at that temperature for 3 hours. The total heating time for the three sections was 8.5 hours.

[0146] 3) Rolling process

[0147] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 150mm×150mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0148] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1000℃, heating time 1.2h; Heating section II temperature 1120℃, heating time 1.3h; Soaking section temperature 1180℃, holding time 1.5h; total heating time 4.0 hours. The initial rolling temperature is 1040℃, and the wire drawing temperature is 925℃.

[0149] About 5 minutes after casting began, severe sintering of the protective slag occurred, with the slag ring forming a crust and the liquid slag layer disappearing. About 10 minutes later, obvious longitudinal cracks appeared on the surface of the cast billet, with a depth of approximately 5-10 mm, forcing a halt to casting. Continuous casting could not proceed smoothly.

[0150] This comparative example demonstrates that existing conventional high-manganese steel protective slag (MnO<10%, Li2O<6%) is not suitable for the continuous casting production of ultra-high alloyed austenitic stainless steel with a total alloy content exceeding 44%, as described in this invention.

[0151] Comparative Example 2

[0152] This comparative example uses the same protective slag as Example 1, but the crystallizer cooling and secondary cooling adopt a strong cooling system to verify the importance of the weak cooling system of the crystallizer and the weak cooling system of the secondary cooling system.

[0153] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.47%, Si 0.13%, Mn 29.7%, Cr 7.1%, Ni 5.4%, Mo 3.5%, P 0.003%, S 0.009%, with the balance being Fe and unavoidable impurities.

[0154] The production method includes:

[0155] 1) Continuous casting process

[0156] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 420mm.

[0157] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 12°C, and the casting speed was 0.40 m / min;

[0158] The crystallizer water flow rate is controlled at 3900 L / min, and the inlet and outlet temperature difference of the cooling water is 6.5℃;

[0159] The insertion depth of the submersible nozzle is controlled to be 190 mm, and the liquid level fluctuation in the crystallizer is controlled to be -5 to +5 mm.

[0160] The protective slag used in the crystallizer comprises the following components and contents: SiO2 28.5%, CaO 24.0%, Al2O3 5.0%, Na2O 9.5%, F - The composition is 6.0%, MnO 12.0%, Li2O 7.0%, MgO 1.8%, Fe2O3 0.8%, C 5.0%, with the balance being unavoidable impurities. The basicity (CaO / SiO2) of the protective slag is 0.84, and the viscosity at 1300℃ is 0.25 Pa·s.

[0161] The second cooling stage adopts a strong cooling water distribution mode, and the specific water volume is controlled at 0.75L / kg;

[0162] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.2mm, 2.8mm, 2.2mm, and 2.8mm for each stage, and a cumulative pressing amount of 10.0mm.

[0163] 2) Heat treatment process

[0164] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 820℃ at a rate of 65℃ / h; the first heating section was heated to 895℃ at a rate of 55℃ / h; the second heating section was heated to 1055℃ at a rate of 85℃ / h; and the third heating section was heated to 1180℃ at a rate of 55℃ / h. After reaching the heating temperature, the billet was held at that temperature for 3 hours. The total heating time for the three sections was 8.5 hours.

[0165] 3) Rolling process

[0166] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 150mm×150mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0167] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1000℃, heating time 1.2h; Heating section II temperature 1120℃, heating time 1.3h; Soaking section temperature 1180℃, holding time 1.5h; total heating time 4.0 hours. The initial rolling temperature is 1040℃, and the wire drawing temperature is 925℃.

[0168] Although no obvious sintering of the protective slag was observed, obvious longitudinal cracks and corner cracks appeared on the surface of the billet, especially in the corner area of ​​the billet, where the crack depth was about 3 to 8 mm, resulting in the billet being substandard.

[0169] This comparative example demonstrates that even with the protective slag designed in this invention (MnO 10~14% + Li2O 6~8%), unreasonable strong cooling of the crystallizer (>3400L / min) and strong cooling of the secondary cooling system (>0.55L / kg) can still lead to crack formation. This indicates that the weak cooling of the crystallizer and the weak cooling of the secondary cooling system proposed in this invention are crucial for the successful continuous casting of ultra-high alloy steel with a solidification range of 102℃.

[0170] Comparative Example 3

[0171] This comparative example uses the same protective slag and cooling system as Example 1, but the superheat of the first furnace casting exceeds the upper limit of the present invention (>15°C) to verify the necessity of controlling the low superheat of the first furnace.

[0172] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.46%, Si 0.15%, Mn 29.3%, Cr 6.9%, Ni 5.2%, Mo 3.3%, P 0.005%, S 0.011%, with the balance being Fe and unavoidable impurities.

[0173] The production method includes:

[0174] 1) Continuous casting process

[0175] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 420mm.

[0176] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 22°C, and the casting speed was 0.40 m / min;

[0177] The crystallizer water flow rate is controlled at 3100 L / min, and the inlet and outlet temperature difference of the cooling water is 4.2℃;

[0178] The insertion depth of the submersible nozzle is controlled to be 190 mm, and the liquid level fluctuation in the crystallizer is controlled to be -5 to +5 mm.

[0179] The protective slag used in the crystallizer comprises the following components and contents: SiO2 28.5%, CaO 24.0%, Al2O3 5.0%, Na2O 9.5%, F - The composition is 6.0%, MnO 12.0%, Li2O 7.0%, MgO 1.8%, Fe2O3 0.8%, C 5.0%, with the balance being unavoidable impurities. The basicity (CaO / SiO2) of the protective slag is 0.84, and the viscosity at 1300℃ is 0.25 Pa·s.

[0180] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.42L / kg;

[0181] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.2mm, 2.8mm, 2.2mm, and 2.8mm for each stage, and a cumulative pressing amount of 10.0mm.

[0182] 2) Heat treatment process

[0183] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 820℃ at a rate of 65℃ / h; the first heating section was heated to 895℃ at a rate of 55℃ / h; the second heating section was heated to 1055℃ at a rate of 85℃ / h; and the third heating section was heated to 1180℃ at a rate of 55℃ / h. After reaching the heating temperature, the billet was held at that temperature for 3 hours. The total heating time for the three sections was 8.5 hours.

[0184] 3) Rolling process

[0185] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 150mm×150mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0186] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1000℃, heating time 1.2h; Heating section II temperature 1120℃, heating time 1.3h; Soaking section temperature 1180℃, holding time 1.5h; total heating time 4.0 hours. The initial rolling temperature is 1040℃, and the wire drawing temperature is 925℃.

[0187] During the casting process, although no obvious sintering of the protective slag occurred, the solidification structure of the billet showed obvious columnar grain coarsening and central segregation. Multiple longitudinal cracks appeared on the surface of the billet, with a crack depth of about 4-7 mm, resulting in the billet failing to meet quality standards.

[0188] This comparative example demonstrates that even with the protective slag and cooling system designed in this invention, a superheat of more than 15°C in the first furnace will still lead to coarsening of columnar crystals, increased central segregation, and crack formation. This indicates that controlling the low superheat of the first furnace (10~15°C) is a key aspect of the overall collaborative design of this invention.

[0189] Comparative Example 4

[0190] This comparative example uses the same protective slag and continuous casting process parameters as Example 1, but the heat treatment heating rate is too fast and the total heating time is insufficient, in order to verify the necessity of the slow heating regime.

[0191] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.48%, Si 0.10%, Mn 29.4%, Cr 7.0%, Ni 5.2%, Mo 3.5%, P 0.004%, S 0.008%, with the balance being Fe and unavoidable impurities.

[0192] The production method includes:

[0193] 1) Continuous casting process

[0194] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 420mm.

[0195] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 12°C, and the casting speed was 0.40 m / min;

[0196] The crystallizer water flow rate is controlled at 3100 L / min, and the inlet and outlet temperature difference of the cooling water is 4.2℃;

[0197] The insertion depth of the submersible nozzle is controlled to be 190 mm, and the liquid level fluctuation in the crystallizer is controlled to be -5 to +5 mm.

[0198] The protective slag used in the crystallizer comprises the following components and contents: SiO2 28.5%, CaO 24.0%, Al2O3 5.0%, Na2O 9.5%, F - The composition is 6.0%, MnO 12.0%, Li2O 7.0%, MgO 1.8%, Fe2O3 0.8%, C 5.0%, with the balance being unavoidable impurities. The basicity (CaO / SiO2) of the protective slag is 0.84, and the viscosity at 1300℃ is 0.25 Pa·s.

[0199] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.42L / kg;

[0200] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.2mm, 2.8mm, 2.2mm, and 2.8mm for each stage, and a cumulative pressing amount of 10.0mm.

[0201] The surface quality of the billet obtained by continuous casting is good, and no cracks are generated.

[0202] 2) Heat treatment process

[0203] The cast billet is not cooled in the pit; it is directly cut and sent into the heating furnace for rapid heating.

[0204] The preheating section temperature is 880℃, and the heating rate is 90℃ / h.

[0205] The heating temperature is 850~1150℃, and the heating rate is 100℃ / h.

[0206] The temperature of the heat spreader is 1180℃, the heating rate is 80℃ / h, and the temperature is held for 1.5 hours after reaching the heat spreader temperature.

[0207] The total heating time for the three stages is 6.5 hours.

[0208] 3) Rolling process

[0209] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 150mm×150mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0210] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1000℃, heating time 1.2h; Heating section II temperature 1120℃, heating time 1.3h; Soaking section temperature 1180℃, holding time 1.5h; total heating time 4.0 hours. The initial rolling temperature is 1040℃, and the wire drawing temperature is 925℃.

[0211] Obvious surface cracks appeared on the billet while it was still in the heating furnace. The cracks were distributed in a network pattern, mainly located in the central and corner areas of the billet surface, with a depth of approximately 4-8 mm. It is speculated that the cracks were caused by excessively rapid heating, resulting in a large temperature difference between the surface and the core (measured temperature difference of approximately 550-700℃), causing thermal stress to exceed the high-temperature strength of the material. After rolling, the cracks further expanded, and the product exhibited severe cracking defects.

[0212] This comparative example demonstrates that even with the protective slag and continuous casting process parameters designed in this invention, an unreasonable heating regime (preheating section temperature > 850℃, excessively fast heating rate, and total heating time < 8h) can still lead to billet cracking, further illustrating the importance of the heating regime in the overall collaborative design.

[0213] Comparative Example 5

[0214] This comparative example uses the same protective slag, continuous casting process parameters, and heat treatment regime as Example 1, but the rolling start temperature is higher than the upper limit of this invention (>1100℃) to verify the necessity of starting temperature control.

[0215] A high-alloy austenitic stainless steel and its production method, wherein the stainless steel comprises, by mass, the following components: C 0.50%, Si 0.09%, Mn 29.6%, Cr 7.3%, Ni 5.7%, Mo 3.8%, P 0.003%, S 0.006%, with the balance being Fe and unavoidable impurities.

[0216] The production method includes:

[0217] 1) Continuous casting process

[0218] The molten steel, obtained through the electric furnace-LF-VD process, with qualified composition, is cast to produce a large square billet with dimensions of 320mm × 420mm.

[0219] As the first batch of molten steel to be poured, the superheat of the molten steel was controlled at 12°C, and the casting speed was 0.40 m / min;

[0220] The crystallizer water flow rate is controlled at 3100 L / min, and the inlet and outlet temperature difference of the cooling water is 4.2℃;

[0221] The insertion depth of the submersible nozzle is controlled to be 190 mm, and the liquid level fluctuation in the crystallizer is controlled to be -5 to +5 mm.

[0222] The protective slag used in the crystallizer comprises the following components and contents: SiO2 28.5%, CaO 24.0%, Al2O3 5.0%, Na2O 9.5%, F- 6.0%, MnO 12.0%, Li2O 7.0%, MgO 1.8%, Fe2O3 0.8%, C 5.0%, with the balance being unavoidable impurities. The basicity of the protective slag (CaO / SiO2) is 0.84, and the viscosity at 1300℃ is 0.25 Pa·s.

[0223] The secondary cooling stage adopts a weak secondary cooling water distribution mode, and the specific water volume is controlled at 0.42L / kg;

[0224] In the light pressing stage, a four-stage pressing mode is adopted, with pressing amounts of 2.2mm, 2.8mm, 2.2mm, and 2.8mm for each stage, and a cumulative pressing amount of 10.0mm.

[0225] 2) Heat treatment process

[0226] The cast billet, after being cooled in the pit, was heated in three sections: the preheating section was heated to 820℃ at a rate of 65℃ / h; the first heating section was heated to 895℃ at a rate of 55℃ / h; the second heating section was heated to 1055℃ at a rate of 85℃ / h; and the third heating section was heated to 1180℃ at a rate of 55℃ / h. After reaching the heating temperature, the billet was held at that temperature for 3 hours. The total heating time for the three sections was 8.5 hours.

[0227] 3) Rolling process

[0228] The heat-treated and cooled billet is heated, and the heated large square billet is rolled into a 150mm×150mm square billet. After rolling, the billet is cooled by a sheltered stacking cooling method.

[0229] After shot blasting, grinding, and inspection, the square billet enters the finished product rolling process. The heating regime is as follows: Heating section I temperature 1000℃, heating time 1.2h; Heating section II temperature 1120℃, heating time 1.3h; Soaking section temperature 1180℃, holding time 1.5h; total heating time 4.0 hours. The initial rolling temperature is 1140℃, and the wire drawing temperature is 935℃.

[0230] During the rolling process, multiple transverse cracks and edge cracks appeared on the surface of the rolled material, with a crack depth of approximately 2-5 mm. Metallographic examination revealed that the austenite grain size was approximately 180-220 μm, exhibiting significant grain coarsening and mixed grain structure. The final product failed to meet the low-temperature impact toughness standard due to surface cracks and coarse grains (impact energy at -196℃ was only 12-18 J, lower than the acceptable value of ≥27 J).

[0231] This comparative example demonstrates that even when using the protective slag, continuous casting process parameters, and heat treatment system designed in this invention, a rolling start temperature exceeding 1100°C will still lead to grain coarsening and surface cracks, and the final product's extremely low temperature impact toughness will not meet service requirements.

[0232] It should be noted that, based on the above embodiments of the present invention, those skilled in the art can fully realize the scope of the independent claims and dependent claims of the present invention, and the implementation process and methods are the same as those in the above embodiments; and the parts of the present invention not described in detail belong to the well-known technology in the art. However, the protection scope of the present invention is not limited thereto, and any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the protection scope of the present invention.

Claims

1. A high-alloy austenitic stainless steel, characterized in that, By mass, it comprises the following components: 0.45-0.55% C, 0.05-0.2% Si, 29-30% Mn, 6-8% Cr, 5-6% Ni, 3-4% Mo, with the balance being Fe and unavoidable impurities.

2. The ultra-high alloyed austenitic stainless steel as described in claim 1, characterized in that, The components also include ≤0.005% P and ≤0.015% S.

3. A method for producing ultra-high alloyed austenitic stainless steel as described in claim 1 or 2, characterized in that, include: 1) Pouring molten steel with qualified composition, wherein, The superheat of the molten steel poured in the first furnace is controlled at 10~15℃, and the superheat of the molten steel poured in the continuous furnace is controlled at 15~35℃. The flow rate of the crystallizer water is controlled at 2800~3400 L / min, and the temperature difference between the inlet and outlet of the cooling water is 3.5~5℃; The protective slag used in the crystallizer comprises the following components and contents: SiO2 24~35%, CaO 20~30%, Al2O3 3.0~7.0%, Na2O 7.5~12%, F - 3.0~9.0%, MnO 10~14%, Li2O 6~8%, MgO≤2.5%, Fe2O3≤1.5%, C 3~17%; 2) In the secondary cooling stage, a weak secondary cooling water distribution mode is adopted, and the specific water volume is controlled at 0.3~0.55L / Kg; 3) In the light pressing stage, a 4-stage pressing mode is adopted, with each stage having a pressing amount of 1.5~3mm.

4. The method as described in claim 3, characterized in that, During the casting process, the insertion depth of the submersible nozzle is controlled to be 160~230mm, and the liquid level fluctuation in the crystallizer is controlled to be -10~+10mm.

5. The method as described in claim 3, characterized in that, During the pouring process, the casting speed is controlled at 0.39~0.42 m / min.

6. The method according to any one of claims 3 to 5, characterized in that, The production method further includes a heat treatment step of cooling the billet, specifically including: heating the billet in three sections, wherein the preheating section temperature is ≤850℃ and the heating rate is ≤70℃ / h, the first heating section temperature is in the range of 850~950℃ and the heating rate is 40~70℃ / h, the second heating section temperature is in the range of 950~1150℃ and the heating rate is 70~100℃ / h, and the soaking section temperature is 1120~1250℃ and the heating rate is ≤60℃ / h. After reaching the target temperature, the holding time is 2~4h, and the total heating time of the three sections is ≥8h.

7. The method according to any one of claims 3 to 5, characterized in that, The production method also includes heating the heat-treated and cooled billet, rolling the heated billet into a square billet with a billet size of (140~160) mm × (140~160) mm, and cooling the billet by a windproof stacking method after billet rolling.

8. The method as described in claim 7, characterized in that, The production method further includes a step of rolling the billet after the initial rolling, specifically including: heating the heat-treated and cooled billet, wherein heating stage I is 930~1050℃ for 1~1.5h, heating stage II is 1000~1220℃ for 1.5~2h, and soaking stage is 1120~1250℃ for 1.5~2h, with a total heating time of 3.5~5.5h, and controlling the initial rolling temperature at 980~1100℃ and the wire drawing temperature at 900~950℃.

9. The method as described in claim 6 or 8, characterized in that, The dimensions of the cast billet are (300~340) mm × (400~500) mm.